GENDER INVOLVEMENT IN COCOA FARMING ACTIVITIES IN SOUTH WEST NIGERIA - Abidogun, O. G.; Olajide, B. R.; Amujoyegbe, B. J.; Bamire, A. S.; Kehinde, A. D.; Gaya, I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
This study investigated gender involvement of household members in cocoa production activities in south west Nigeria. A multi-stage sampling procedure was used to randomly select respondents from cocoa producing states in south-western Nigeria; specifically, Oyo and Osun states. Four field sites namely Iddo and Ogo-Oluwa in Oyo State and Atakumosa East and Ayedire in Osun state were purposively selected due to the on-going humidtropics project in these states. Fifty cocoa farmers registered with the state Agricultural Development Programme (ADP) who were members of the Innovation Platform (IP) in the on-going humid tropics programme were purposively selected from each of the 4 field sites from Akindele, Lagbedu and Iwara, Osunwoyin in Oyo and Osun States respectively, making a total of 200 cocoa farmers comprising 147 males and 53 females.  Data were analyzed using descriptive (frequency and percentage) and inferential (Chi-square and PPMC) statistics at p=0.05. Descriptive result revealed that majority 73.5% and 89.5% of the respondents were male and married. While 40.0% were primary school leavers. The respondents’ mean age and years of farming experience were 52 years and 29 years, respectively. It further revealed that the head of the family took most decisions on different production activities such as, crops to plant (68%), technology to be adopted (55%), purchase of inputs (55%) and varieties to grow (66%). There was a significant relationship between respondents’ personal characteristics such as educational qualification and household size (ϰ2 = 408.518, r = 0.347), and their involvement in cocoa production activities. Further result shows a significant difference between male and female involvement in cocoa production activities (t= 2.304, p= 0.022). The study concluded that women were less involved in most production activities. It is therefore recommended that government should encourage women to be more involved in production activities. In terms of technical know-how, training on proper use and maintenance of such technology should be provided.